Invasive pneumococcal disease in Latin America and the Caribbean: Serotype distribution, disease burden, and impact of vaccination. A systematic review and meta-analysis - Bardach, Ariel Esteban (2024)
Background: Invasive pneumococcal diseases (IPD) are associated with high morbidity, mortality, and health costs worldwide, particularly in Latin America and the Caribbean (LAC). Surveillance about the distribution of serotypes causing IPD and the impact of pneumococcal vaccination is an important epidemiological tool to monitor disease activity trends, inform public health decision-making, and implement relevant prevention and control measures.Objectives: To estimate the serotype distribution for IPD and the related disease burden in LAC before, during, and after implementing the pneumococcal vaccine immunization program in LAC.Methods: Systematic literature review following Cochrane methods of studies from LAC. We evaluated the impact of the pneumococcal vaccine on hospitalization and death during or after hospitalizations due to pneumococcal disease and serotype-specific disease over time. We also analyzed the incidence of serotyped IPD in pneumococcal conjugate vaccine PCV10 and PCV13. The protocol was registered in PROSPERO (ID: CRD42023392097).Results: 155 epidemiological studies were screened and provided epidemiological data on IPD. Meta-analysis of invasive diseases in children <5 years old found that 57%-65% of causative serotypes were included in PCV10 and 66%-84% in PCV13. After PCV introduction, vaccine serotypes declined in IPD, and the emergence of non-vaccine serotypes varied by country.Conclusions: Pneumococcal conjugate vaccines significantly reduced IPD and shifted serotype distribution in Latin America and the Caribbean. PCV10/PCV13 covered 57-84% of serotypes in children under 5, with marked decline in PCV serotypes post-vaccination. Continuous surveillance remains crucial for monitoring evolving serotypes and informing public health action.